Study Content Nutrient Waste Plant Seeds Nyamplung (Calophyllum inophyllum Linn) after Made as Biofuel - Tri Mulya Hartati (Fakultas Pertanian Universitas Tanjungpura, 2012)
Determination revoke government fuel subsidies in 2008, with all its consequences have begun to be realized by finding various solutions techno-socio-economic development. Among the various solutions that are developing alternative fuel made from vegetable oils or biofuels. This is demonstrated by the issuance of Presidential Regulation No. 5/2006 on National Energy Policy and Presidential Instruction No. 1/2006 on the Provision and Use of Biofuels (Biofuel) as an alternative fuel on January 25, 2006. Biofuel Excess addition can also be environmentally friendly renewable, biodegradable, able to eliminate the greenhouse effect, and continuity is assured raw material. Bioenergy can be obtained with a fairly simple way is through the cultivation of biofuel crops, have recently discovered a new source of biofuel that is nyamplung (Calophyllum inophyllum Linn). Nyamplung is a plant that grows in coastal forests. As with other agricultural residual waste, waste from the process of making biofuels from plants also contain nutrients that can be used as a soil or as a source of fertilizer for plants. This study aims to assess the nutrient content of the waste content of seeds nyamplung (Calopphyllum inophyllum Linn) after it is created as a Biofuel. The results showed that the biofuel seed crop nyamplung (Calopphyllum inophyllum Linn) have oil content of 46.57%, and biofuels from waste plant seeds contain nutrients: total N 1.43% (very high), 47.99% Organic C ( very high), total P 0.35% (very low), 1.30% total K (very low), C / N 33.78 (very high), and 17.93 KPK to 100 g-1 (medium). Key words: oil nyamplung, nutrient waste plant seeds nyamplung